Coil member and method for manufacturing the same, and armature

The development of a coil member with a high-porosity anodic oxide film on an aluminum-based conductor addresses the limitations of existing coils, achieving improved insulation, reduced dielectric loss, and enhanced efficiency in electromagnetic devices.

JP2025038361APending Publication Date: 2025-03-19KK TOYOTA CHUO KENKYUSHO +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023144917
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-19

AI Technical Summary

Technical Problem

Existing coils made of continuous conductors have limitations in improving space factor and efficiency, and conventional anodic oxide films used in segment conductors do not achieve high porosity, leading to suboptimal insulation and efficiency in electromagnetic devices.

Method used

A coil member with an insulating film made of an anodic oxide film formed on an aluminum-based conductor, featuring a porosity of 20-75%, which provides excellent insulation and low dielectric loss, along with a manufacturing method using a phosphoric acid electrolyte to maintain high porosity.

Benefits of technology

The high-porosity anodic oxide film enhances insulation properties, reduces dielectric loss, and improves the reliability and efficiency of electromagnetic devices, such as electric motors, by maintaining high voltage resistance and flexibility even at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038361000001_ABST
    Figure 2025038361000001_ABST
Patent Text Reader

Abstract

To provide a coil member which achieves reduction in a weight of a coil and a low loss.SOLUTION: A coil member includes a conductor composed of an Al base material, and an insulating film coating at least a part of the conductor. The insulating film has an anode oxide film formed on the Al base material, and the anode oxide film has a porosity determined by observing the upper surface of 20 to 75%. The anode oxide film has, for example, film thickness of 20 to 150 μm. The anode oxide film may have a main hole extending in a substantially straight shape from the Al base material side, and an auxiliary hole opened at a part of a side wall of the main hole. The insulating film further may have a resin layer on the anode oxide film. The resin layer has, for example, thickness of 1 to 20 μm. The coil member is, for example, a segment conductor fit and inserted to a slot of a stator core of a motor.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coil member or the like made of an insulating-coated Al-based conductor. [Background technology]

[0002] There are various types of electromagnetic devices that have an armature and a field magnet. A typical example is an electric motor (including a generator). There are various types of electric motors that have a rotor and a stator, such as rotating armature types and rotating field types. There are also inner rotor types in which the rotor rotates on the inner circumference of the stator, and outer rotor types in which the rotor rotates on the outer circumference of the stator. However, all electric motors have in common the fact that they have at least one coil assembled in a core.

[0003] Electric motors installed in moving objects such as vehicles are required to be compact, lightweight, high output, highly efficient (low loss), etc. To achieve these goals, many efforts have been made to improve the coil space factor, reconsider winding methods, and improve the coil wire (materials).

[0004] There is a limit to how much improvement can be made to coils made of continuous conductors. For this reason, coils made of segment conductors are being considered, and the following non-patent literature contains a description of this. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Masashi Yamamura et al.: Technological Trends of Automotive Motors, DENSO Technical Review, vol. 23 (2018) [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2000-349320 [Patent Document 2] Patent Publication No. 2004-59997 [Patent Document 3] Patent Publication No. 2011-117042 [Patent Document 4] Patent Publication No. 2018-44227 Summary of the Invention [Problem to be solved by the invention]

[0007] Non-Patent Document 1 relates to a segment conductor made of coated copper wire.

[0008] Patent documents 1 to 4 are all directed to wiring boards, semiconductor elements, etc., and make no mention of coils through which a large current flows in an alternating magnetic field. Patent documents 1 to 4 merely use a general form of anodic oxide film obtained by electrolysis in a bath of sulfuric acid or oxalic acid as the insulating film.

[0009] The present invention has been made in view of the above circumstances, and has an object to provide a novel coil member or the like made of an insulating coated Al-based conductor. [Means for solving the problem]

[0010] As a result of intensive research into solving the above problems, the inventors of the present invention discovered a new anodic oxide film suitable for use as an insulating film for coils. By expanding on this discovery, the inventors have completed the present invention, which will be described below.

[0011] <Coil components> (1) The coil member of the present invention is a coil member comprising a conductor made of an aluminum base (Al base) and an insulating film covering at least a part of the conductor, the insulating film having an anodized film formed on the Al base, and the anodized film having a porosity of 20 to 75% as determined by observing the top surface of the coil member.

[0012] (2) According to the present invention, it is possible to provide a coil that can achieve high insulation (voltage resistance, insulation life, etc.) or high efficiency (low loss), etc. The reasons for this are considered to be as follows.

[0013] The anodic oxide film according to the present invention has a significantly higher porosity than conventional anodic oxide films. An insulating film having such an anodic oxide film has a very small (relative) dielectric constant, and is not only excellent in insulation but also can significantly reduce dielectric loss when AC is applied (see the formula in FIG. 5).

[0014] Furthermore, the highly porous anodized film is highly flexible and is less likely to crack even in a high-temperature environment, so the insulating film according to the present invention can stably exhibit high insulating properties.

[0015] <<Manufacturing method of coil components, etc.>> The present invention can also be understood as a method for producing a coil member. For example, the present invention may be a method for producing the coil member described above, comprising an electrolysis step of applying a current to an Al base material that is in contact with an electrolytic solution containing phosphoric acid.

[0016] When the electrolyte contains phosphoric acid, an anodized film with high porosity is easily formed. In addition, the surface of the anodized film is covered with an insoluble phosphate film, which inhibits natural sealing of the anodized film (hydration reaction with moisture in the air), and the high porosity of the anodized film is easily maintained. Therefore, the above-mentioned manufacturing method can provide a coil member that can contribute not only to improving the characteristics of the coil (and thus the electric motor, etc.) but also to ensuring the reliability.

[0017] 《Electromagnetic equipment, etc.》 The present invention can also be understood as a coil manufactured using the above-mentioned coil member, an electromagnetic device (e.g., an electric motor) including the coil, a component thereof (e.g., an armature), etc. One example is an armature in which the above-mentioned coil member is inserted into a slot in a core.

[0018] It should be noted that the armature referred to in this specification is not limited to that used in electric motors (including generators). If the armature is used in an electric motor, it may be a stator, a rotor, or both. The electric motor may be a DC motor or an AC motor. The electric motor may be a synchronous machine or an asynchronous machine (such as an induction machine). For example, the coil member of the present invention may be used in the rotor of an induction machine. The induction machine may be a squirrel-cage type or a wound type.

[0019] "others" In this specification, "x to y" includes a lower limit value x and an upper limit value y unless otherwise specified. Any numerical value included in the various numerical values ​​or numerical ranges described in this specification may be used as a new lower limit or upper limit value to create a new range such as "a to b". In addition, in this specification, "α to β μm" means α μm to β μm unless otherwise specified. The same applies to other units (nm, etc.). [Brief description of the drawings]

[0020] [Figure 1] This is an SEM image of the insulating film (anodic oxide film) observed from the top. [Diagram 2] This is an SEM image of the upper side of the fracture surface. [Figure 3A] This is an SEM image of the upper side of a fracture surface of an insulating film (anodic oxide film and resin layer). [Figure 3B] This is an SEM image of the underside (bottom side) of the fracture surface. [Figure 4] FIG. 1 is a schematic diagram showing a manufacturing process of a stator incorporating a segment conductor. [Diagram 5] This is a formula for calculating the relative dielectric constant (εi) and the withstand voltage (V) of an insulating layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The contents described in this specification may be applicable not only to the product of the present invention but also to the method as appropriate. One or more components selected arbitrarily from this specification may be added to the components of the present invention. Which embodiment is best depends on the target, required performance, etc.

[0022] <Anodic oxide film> (1) Ingredients The anodic oxide film is mainly made of aluminum oxide (Al 2 O 3) The anodized film may contain components derived from the composition of the electrolyte. For example, if an electrolyte containing phosphoric acid is used, P, H, etc. may be contained in the anodized film. In addition, phosphates (e.g., Al-PO compounds, Al-POH compounds) may be present near the surface of the anodized film.

[0023] Incidentally, an anodic oxide film is different from a plating film (layer) that simply covers a substrate in that it is produced by an anodizing process that involves oxidation of the Al substrate itself. Conventional anodic oxide films have a dense and thin barrier layer (active layer) and a porous layer (growth layer) grown on the barrier layer, and the porous layer is usually mostly made up of micropores (groups) that are approximately straight tube (cylinder) shaped and open on the surface side. It is difficult to achieve a high porosity with such a general anodic oxide film. In this specification, the term "approximately α-shaped" means that the overall appearance is α-shaped when the actual product or a micrograph is visually observed, and does not have to be an ideal linear shape (e.g., a straight line) or angular shape (e.g., a right angle). The same applies to "approximately orthogonal" and the like. To give a specific example, a coil that is "approximately rectangular" usually has more or less rounded corners (corner R) at the corner apexes of the cross section, and the cross section is rarely a strict rectangle in geometry.

[0024] (2) Porosity The porosity of the anodized film according to the present invention is, for example, 20 to 75%, 30 to 65%, 40 to 55%, or 43 to 50%. Such a large porosity is not observed in conventional anodized films made of a porous layer having columnar holes (cells). Anodized films with a large porosity are excellent in flexibility and are less likely to crack even when exposed to a high-temperature environment. In addition, such anodized films have high voltage resistance characteristics and a low relative dielectric constant. For this reason, they are suitable for insulating films of conductors (for example, coil members in an alternating magnetic field) through which high-frequency (for example, 0.1 to 30 kHz, 1 to 15 kHz) and high-voltage AC currents are passed. A detailed method for calculating the porosity will be described later.

[0025] (3) Main hole and sub-hole The highly porous anodized film may have main holes extending in a substantially straight tube shape from the Al substrate side, and sub-holes opening in part of the side walls of the main holes. The details of the main holes and sub-holes are as follows.

[0026] The main hole is, for example, a bottomed cylindrical shape extending from the bottom on the Al substrate side to the opening at the top. The form (shape, size) of the hole may vary somewhat along the vertical direction (depth direction, axial direction, or extension direction). The opening diameter of the main hole is, for example, 50 to 1000 nm, 100 to 500 nm, or 150 to 350 nm. Such an opening diameter (also called "opening diameter") is usually significantly larger than conventional columnar holes (cells).

[0027] For example, the sub-holes open in a part of the side wall of the main hole and extend in the horizontal direction (the direction substantially perpendicular to the side wall of the main hole). At least a part of the sub-holes may penetrate the side wall of the main hole (connect adjacent main holes). The distribution of the sub-holes may be uniform or non-uniform along the vertical direction in which the main hole extends.

[0028] There should be at least one sub-hole in the field of view when the anodized film is observed from the side. Furthermore, it is desirable that there is at least one surface region (depth 1 μm × width 10 μm) containing one or more, three or more, or even five or more sub-holes in the field of view.

[0029] The porosity and opening diameter referred to in this specification are specified based on an image (observation image) obtained by observing the anodized film with a microscope. The porosity is the ratio of the pore area (total value) to the total area of ​​the anodized film in the field of view observed from the top side. The opening diameter is the average arithmetic value of the circle equivalent diameter of each pore in the same field of view. The porosity and opening diameter are calculated, for example, by image analysis software (Image J). The field of view (evaluation range) of the observation image does not matter, but may be, for example, 5×4 μm to 12.7×8.8 μm. The presence or absence (number) and shape of the sub-holes may be visually confirmed based on the surface observation image of the anodized film. Of course, they may be evaluated based on the observation image of the vertical cross section (for example, a cut surface or a fracture surface in the film thickness direction) of the anodized film. In this case, it is preferable that the sub-holes are evaluated at least in the surface layer region of the anodized film (for example, a region 10 μm deep from the outermost surface).

[0030] In this specification, for convenience of explanation, the surface side of the anodic oxide film (the opening side of the main hole) is referred to as the upper side, and the opposite side (the Al base material side) is referred to as the lower side or bottom side. The thickness direction of the anodic oxide film is also referred to as the vertical direction, and the direction approximately perpendicular to the vertical direction is also referred to as the horizontal direction.

[0031] (4) Film thickness The anodized film has a thickness of, for example, 20 to 150 μm, 30 to 100 μm, or 35 to 70 μm. The thickness of the anodized film includes the thickness of the so-called barrier layer. The thickness of the barrier layer is, for example, 10 to 1000 nm, 50 to 500 nm, or 100 to 300 nm. The group of main holes formed on the barrier layer is also referred to as a "porous layer" in this specification as appropriate.

[0032] The thickness of the anodic oxide film (film thickness) in this specification is measured by a film thickness meter unless otherwise specified. The film thickness may be determined as the distance (average value) from the bottom surface of the anodic oxide film (the bottom surface of the barrier layer) to the top surface (the top surface of the porous layer) based on the observed image.

[0033] Resin layer A resin layer may be formed on the anodized film. The resin layer can prevent the anodized film from absorbing moisture and can increase the withstand voltage of the insulating film.

[0034] The resin layer is preferably a resin having excellent heat resistance and a small (relative) dielectric constant. Such a resin may be a thermoplastic resin or a thermosetting resin. For example, polyimide, polyamideimide, polyesterimide, epoxy, polyvinylformal, polyurethane, polyester, or the like may be used.

[0035] The resin layer is usually thinner than the anodized film. There is no specific limit to the thickness, but it may be, for example, 1 to 35 μm, 5 to 30 μm, or 10 to 20 μm. It is preferable that the resin layer does not penetrate deep into the anodized film, but leaves voids in the anodized film, thereby ensuring a high porosity. This improves the withstand voltage of the insulating film and reduces dielectric loss. Note that, as long as a high porosity is ensured, a sealing treatment or a sealing treatment may be performed instead of or together with the formation of the resin layer.

[0036] The main holes that open to the surface side and the sub-holes on the surface side can increase the adhesion of the resin layer to the anodized film due to the anchor effect, etc. Therefore, it is preferable that many larger sub-holes are distributed on the surface side.

[0037] The resin layer is formed on the anodized film by, for example, applying, spraying, dipping, or electrodeposition of an electrical insulating paint (varnish). The drying and curing are performed according to the type of resin, but for example, heat drying or heat curing is preferable. In other words, a resin coating process is performed in which the resin is applied onto the anodized film and then heated. The moisture and other substances adsorbed on the anodized film are removed by heating.

[0038] 《Al base material》 The Al base material may have any composition as long as it has excellent electrical conductivity and does not inhibit the formation of a highly porous anodized film. For example, pure Al (JIS A1000 series, etc.) containing 98 mass% or more, 98.5 mass% or more, 99 mass% or more, or even 99.6 mass% or more of Al may be used as the Al base material.

[0039] The Al base material may be, for example, an Al alloy or pure Al having a conductivity of 50% IACS (International Annealed Copper Standard) or more, 55% IACS or more, or even 60% IACS or more. "% IACS" refers to the electrical conductivity of annealed standard soft copper (volume resistivity: 1.7241×10 -8 It is a relative index (ratio) to the electrical conductivity (100% IACS) of Ωm. The Al base material may be, for example, a wrought material or a cast material.

[0040] Anodizing The anodic oxide film is formed by an electrolytic process in which electricity is passed through an Al base material in contact with an electrolyte. By anodizing an Al base material that has been formed or processed into a desired shape, it is possible to prevent cracks in the anodic oxide film (insulating film).

[0041] (1) Electrolyte As long as an anodic oxide film of a desired shape is formed, the composition of the electrolyte is not limited. The electrolyte may be, for example, an inorganic acid solution (such as an aqueous phosphoric acid solution, an aqueous sulfuric acid solution, or an aqueous chromic acid solution) or an organic acid solution (such as an aqueous oxalic acid solution).

[0042] When an electrolyte containing phosphoric acid is used, the concentration of phosphoric acid may be, for example, 1 to 30%, 2 to 20%, or 3 to 10%. In this specification, the concentration of the electrolyte is a mass ratio to the whole, unless otherwise specified. The temperature of the electrolyte (bath temperature) may be, for example, 15 to 80°C, 20 to 60°C, or 25 to 40°C.

[0043] (2)Electricity The electrolysis process is performed, for example, by constant current or constant voltage energization. The current (density) or applied voltage may change (fluctuate) during energization. The electrolysis process may be performed by direct current, alternating current, or superimposed AC / DC energization combining AC and DC components. The waveform of the alternating current may be a sine wave, a square wave, a pulse wave, or the like.

[0044] When the electrolysis step is carried out by direct current, for example, a high voltage of about 30 to 250 V, 40 to 200 V, or even 75 to 175 V may be applied to the Al base material at least temporarily. There is no particular restriction on the counter electrode provided in the electrolytic solution, but a platinum electrode, a graphite electrode, or the like is usually used.

[0045] <Coil components> The specific form (shape or size) of the coil member is not important. The coil member may be a continuous conductor or a divided conductor. The use of divided conductors improves the freedom of shape of the coil and the space factor. One example of a divided conductor is a segment conductor that is inserted into a slot of a core (e.g., a stator core or a rotor core). A segment conductor is connected to another segment conductor at its adjacent end to form a coil. The end of such a segment conductor may not have an insulating coating. At such an end, no insulating film may be provided, or the insulating film may be peeled off. The joint (connection) between the end portions is performed, for example, by welding, melting, or the like. The cross-sectional shape of the segment conductor may be (elliptical) circular, but a square shape (particularly a substantially rectangular shape) improves the space factor.

[0046] Such a segment conductor may be used, for example, in an armature (particularly a stator) of a high-output motor for an electric vehicle (including a hybrid vehicle) or the like. EXAMPLES

[0047] Assuming that the segment conductor (SC) to be incorporated in the stator of a motor is used, several types of samples were produced by forming an anodized film on the surface of an aluminum base material (conductive material) with a rectangular cross section, while changing the manufacturing conditions. The present invention will be described in more detail with the following concrete examples.

[0048] [First Example / Constant Current Electrolysis] <Sample Preparation> (1) Test piece A test piece (simply referred to as "Al piece") made of pure aluminum (JIS A1050) and having a rectangular cross section (50 mm square × 2 mm thick) was prepared.

[0049] (2) Anodizing (electrolysis process) The Al pieces were subjected to an electrolysis process under the conditions shown in Table 1. An aqueous solution of phosphoric acid, sulfuric acid or oxalic acid was used as the electrolyte. The concentrations shown in Table 1 are the mass ratios to the entire aqueous solution.

[0050] The aluminum piece was immersed in its entirety in a treatment bath containing an electrolytic solution, and a constant current (density) direct current was applied to the aluminum piece as the anode and a stainless steel piece (JIS SUS304) as the cathode while stirring the electrolytic solution. The current density was 30 mA / cm. 2 The current density was determined by dividing the applied current by the treated area of ​​the aluminum piece. 2 ) was kept constant by masking a part of the aluminum piece. Since the applied voltage fluctuates during electrolysis, for reference, the measured voltage 10 minutes after the start of current application is also shown in Table 1.

[0051] After the electrolysis process, the Al pieces were removed from the electrolyte and washed thoroughly with distilled water, then compressed air was blown onto them to remove moisture, and they were then thoroughly dried in the air. In this way, three types of sample groups A, B, and C shown in Table 1 were obtained. Samples A1, B1, and C1 were Al pieces covered only with an anodic oxide film.

[0052] (3) Formation of resin layer (resin coating process) In addition, samples were prepared in which two types of resin layers were formed on each anodized film. The first, samples A2, B2, and C2, were prepared by spraying a commercially available non-photosensitive polyimide varnish onto each anodized film (application step) and then thermally curing the varnish by heating in an oven (350°C x 1 hour) (thermal curing step) to form resin layer 1.

[0053] The other samples are samples A3, B3, and C3, in which a commercially available photosensitive polyimide varnish was sprayed onto each anodized film (application process), and then thermally cured by heating in an oven (200°C x 1 hour) (thermal curing process) to form a resin layer 2.

[0054] For comparison, a sample D was also produced in which a resin layer 2 was formed in the same manner on the surface of an Al piece that had not been subjected to anodizing treatment. However, the resin layer 2 of sample D was formed thickly by repeatedly applying a photosensitive polyimide varnish.

[0055] The resin layer of each sample was visually inspected for the presence or absence of cracks, and the results are shown in Table 1.

[0056] Observation and Measurement (1) Surface observation The surfaces (top surfaces) of the anodic oxide films of samples A1, B1, and C1 were observed using a scanning electron microscope (SEM / S-5500 manufactured by Hitachi High-Technologies Corporation). The SEM images are shown in Figure 1.

[0057] (2) Fracture surface observation The longitudinal cross sections (coating cross sections) of the surface side obtained by tensile breaking of each sample were similarly observed by SEM. SEM images of samples A1, B1, and C1 are shown together in Figure 2. SEM images of samples A2, B2, and C2 are shown together in Figures 3A and 3B (collectively referred to as "Figure 3"). Figure 3A shows the top side of the coating, and Figure 3B shows the bottom side.

[0058] Based on each SEM image, the presence or absence of sub-holes (horizontal holes) in the region 1 μm deep from the outermost surface of the anodic oxide film (surface layer region) was visually confirmed. The results are also shown in Table 1.

[0059] (3) Film thickness The thickness of the anodic oxide film and resin layer formed on the surface of each sample was measured using an eddy current film thickness meter (SWT-9200, manufactured by Sanko Electronics Laboratory Co., Ltd.). The measurements were carried out after the electrolysis process and after the resin coating process. The thickness of the resin layer was calculated by subtracting the former thickness from the latter thickness. The obtained film thicknesses are also shown in Table 1.

[0060] (4) Dielectric constant The relative dielectric constants of the coatings (insulating layers) of the samples A1, A2, B1 and C1 were determined as follows, and the results are shown in Table 1.

[0061] The capacitance between the upper electrode (Cu plate: φ8.5 mm) placed on the coating of each sample and the lower electrode consisting of an Al piece (anodized specimen) was measured with an LCR meter (IM3536 / 3531Z manufactured by Hioki E.E. Corporation). The measurement environment was 24°C x 30% RH (relative humidity).

[0062] The arrangement of the upper electrode was changed to five different locations (arbitrary), and the measurement was repeated to obtain the average capacitance (C [F]). Using this average value, the relative dielectric constant (ε r ) was calculated. C=ε r ε 0 (S / t) ε 0 : Dielectric constant of vacuum (=8.854×10 -12 F / m) S: Area of ​​upper electrode [m 2 ] t: Electrode spacing [m] The electrode gap was measured by the above-mentioned method. For sample A2, the total thickness of the anodized film and the resin layer 1 was used.

[0063] <Voltage resistance test> The samples A3, B3, C3 and D were subjected to the following withstand voltage test.

[0064] Using a variable frequency withstand voltage test power supply (DAC-WT-25 manufactured by Soken Denki Co., Ltd.), a sine wave voltage (800V, 1kHz) was applied between a ball electrode (φ20mm) placed on the coating of each sample and an Al piece (anodized test piece). The test environment was 30℃×50%RH (relative humidity). After the start of the test (voltage application), the time until the breaking current exceeded 50mA was measured and this was taken as the dielectric breakdown life. The results are also shown in Table 1.

[0065] Image Analysis The porosity and opening diameter (aperture diameter) of the anodized films of the samples A1, B1 and C1 were determined by analyzing the SEM images (see FIG. 1). The specific calculation method is as follows.

[0066] (1) Porosity The SEM images were adjusted to include 10 or more main holes in one field of view, and were converted to 8-bit format using ImageJ (free software), and binarized to extract holes that were open on the surface. After processing each hole with the Watershed Algorithm, the area of ​​the opening was 100 nm 2The total opening area of ​​the holes was calculated. The ratio of the total area to the total field of view was defined as the porosity. In this example, the field of view of sample A1 was 1280 nm × 890 nm, and the field of view of samples B1 and C1 was 640 nm × 445 nm.

[0067] (2) Opening diameter For the SEM images used to measure the porosity, the maximum diameter (maximum length) of each of the 10 main pores randomly selected was measured, and the arithmetic average value was taken as the aperture diameter. For both the porosity and the aperture diameter, the same operation (analysis and measurement) was performed on five SEM images. The average values ​​of the five SEM images thus obtained are also shown in Table 1.

[0068] "evaluation" (1) Anodic oxide film As can be seen from Table 1, the anodic oxide film (sample A1) formed by applying a high voltage in an electrolyte containing phosphoric acid had a significantly larger porosity and opening diameter than the other samples B1 and C1.

[0069] As is clear from Figures 1 and 2, the anodized film of sample A1 had a large main hole extending in a substantially straight tube shape from the Al piece (Al substrate) side, as well as many thin sub-holes that opened into the side walls of the main hole. As is clear from Figures 3A and 3B, the sub-holes were larger in the upper layer region (1 μm deep) than in the lower layer region (bottom side, barrier layer side), and their density also tended to increase from bottom to top. Such a unique morphology was not observed in the anodized films of other samples.

[0070] (2) Resin layer As shown in Table 1, no cracks were observed in the resin layers of samples A2 and A3, whereas cracks were observed in the resin layers of samples B2, B3, C2 and C3.

[0071] During the thermal curing process of the resin layer, thermal stress is generated between the aluminum pieces and the anodized film due to the difference in thermal expansion coefficients, and it is believed that this thermal stress causes cracks in the anodized film to propagate to the resin layer.

[0072] The anodized films of samples A2 and A3 have main pores with large porosity and large opening diameters, as well as sub-pores on the side walls. Such anodized films are highly flexible and therefore less likely to crack even when exposed to high temperatures, and have excellent crack resistance.

[0073] (3) Adhesion As can be seen from Figure 3, the resin layer of sample A2 penetrated into the surface layer side of the anodized film (to a depth of about 1 μm) and was in a state of being engaged in the main and sub-holes. This situation was hardly observed in the anodized films of the other samples.

[0074] The SEM image in Figure 3 shows the tensile fracture surface. Part of the resin layer of sample A2 remained on the anodized film even after fracture. On the other hand, the resin layers of samples B2 and C2 were not in close contact with the anodized film, and peeled off entirely from the anodized film upon fracture.

[0075] Incidentally, as can be seen from the SEM images of sample A2 shown in Figures 3A and 3B, the resin layer only engaged with the top of the anodic oxide film, and did not penetrate (penetrate) to the bottom. This is thought to be why sample A2 exhibited the low (relative) dielectric constant (high insulation) described later, along with the high adhesion of the resin layer.

[0076] (4) Dielectric constant As shown in Table 1, the dielectric constant of sample A1 is approximately 30 to 40% smaller than that of samples B1 and C1. This is thought to be because the porosity of the anodized film of sample A1 was greater than that of the other samples. The relationship between the porosity and the dielectric constant of the anodized film (insulator) can also be explained by the ASWindeler formula. The relationship between the dielectric constant and the withstand voltage can be understood from the Dakin formula. The sources of each formula shown in Figure 5 are as follows: [1] Windeler, AS, “Polyethylene Insulated Telephone Cable”, The Bell System Technical Journal, Vol.32, No.5(1953), pp.1245-1256. [2] Dakin, TW, Philofsky, HM, Divens, WC, “Effect of electric discharges on the breakdown of solid insulation”, Transactions of the American Institute of Electrical Engineers, Part 1: Communication and Electronics, Vol.73, No.2(1954), pp.155-162.

[0077] Sample A2, in which a resin layer was formed on the anodized film of sample A1, had a dielectric constant that was further reduced by about 40 to 50%. This is thought to be because the moisture adsorbed on the anodized film was desorbed by heating (thermal curing treatment) during the formation of the resin layer, and the resin layer prevented moisture from penetrating the anodized film.

[0078] In this way, it was found that an insulating film with a low relative dielectric constant can be formed on an Al-based conductor by forming a resin layer on a highly porous anodized film using a highly viscous varnish, etc. Based on these results, it is preferable that the relative dielectric constant of the insulating film is, for example, 5 or less, 4 or less, 3.5 or less, 3 or less, or 2.5 or less.

[0079] (5) Voltage resistance characteristics As shown in Table 1, sample A3 had a significantly longer dielectric breakdown life than samples B3, C3, and D, and exhibited high voltage resistance characteristics. The endurance test for sample A3 was terminated because the interrupting current did not exceed 50 mA even after 8,278 minutes (approximately 5.75 days) had elapsed. It was also found that a coating made of an anodized film and a resin layer, such as sample A3, exhibits significantly better insulation durability than a single layer polyimide film, such as sample D. Incidentally, it is believed that sample B3 did not exhibit any insulation properties at all due to cracks in the coating.

[0080] From the above, it has been confirmed that the anodized film according to the present invention has a high porosity and a unique morphology, and contributes to high adhesion to a resin layer, a low (relative) dielectric constant, high voltage resistance, etc. Such an anodized film is suitable for an insulating film or an underlayer of an Al-based conductor.

[0081] Split Conductor As an example of the coil wire of the present invention, a segment conductor 1 forming an armature coil is shown in FIG.

[0082] The segment conductor 1 is formed by coating an Al-based conductor 2, which is a wire material with a rectangular cross section formed into a substantially U-shape, with an insulating film 3 consisting of an anodic oxide film 31 and a resin layer 32. However, each end 12 of the segment conductor 1 is not insulated. Such ends may be formed by devising a method of masking the Al-based conductor or immersing it in an electrolyte, or may be formed by partially peeling off an insulating film that has been formed.

[0083] The segment conductor 1 is inserted into slots a of the motor's stator core C. The number of slots that one segment conductor 1 spans and the number of segment conductors inserted into one slot are adjusted according to the number of poles of the stator core, the winding method of the coil, etc.

[0084] An end of the segment conductor 1 inserted into the stator core C is joined to an end of another adjacent segment conductor 1. Examples of joining methods include welding by laser irradiation and fusion by resistance heating.

[0085] In this way, a stator S is obtained in which the coil L is provided on the stator core C. A motor equipped with such a stator has a high coil space factor and is lightweight, and its insulating film has a low dielectric constant and high withstand voltage, so that it has low loss, good efficiency, and high reliability.

[0086] [Table 1] [Explanation of symbols]

[0087] 1 Segment conductor (coil member) 2. Al-based conductor 3. Insulating film 31 Anodic oxide film 32 Resin layer C Stator Core L coil S stator

Claims

1. A coil member comprising a conductor made of an aluminum base material (referred to as an "Al base material") and an insulating film covering at least a portion of the conductor, The insulating film has an anodized film formed on the Al base material, The anodic oxide film is a coil member having a porosity of 20 to 75% as determined by observing the top surface.

2. 2. The coil member according to claim 1, wherein the anodic oxide film has a thickness of 20 to 150 μm.

3. 2. The coil member according to claim 1, wherein the anodized film has a main hole extending in a substantially straight tube shape from the aluminum base side and a sub-hole opening in a part of a side wall of the main hole.

4. 4. The coil member according to claim 3, wherein the main hole has an opening diameter of 50 to 1000 nm.

5. The coil member according to claim 3 , wherein at least a portion of the sub-hole extends through a side wall of the main hole.

6. The coil member according to claim 1 , wherein the insulating film further comprises a resin layer on the anodized film.

7. The coil member according to claim 6 , wherein the resin layer is thinner than the anodized film.

8. 7. The coil member according to claim 6, wherein the resin layer is made of polyimide, polyamideimide, polyesterimide, epoxy, polyvinylformal, polyurethane or polyester.

9. The coil member according to claim 1 , wherein the Al base contains 98 mass % or more of Al based on the entirety of the Al base.

10. 2. The coil member according to claim 1, which is a segment conductor inserted into a slot of the core.

11. The coil member according to claim 10 , wherein the ends of the segment conductors are not insulated.

12. The coil member according to claim 10 , wherein the segment conductor has a cross section that is substantially rectangular.

13. An electrolysis step is provided in which an electric current is applied to the Al base material that is in contact with an electrolytic solution containing phosphoric acid; A manufacturing method for obtaining the coil member according to any one of claims 1 to 12.

14. The method for manufacturing a coil member according to claim 13, further comprising a resin coating step of applying a resin onto the anodic oxide film and heating the resin.

15. An armature comprising the coil member according to any one of claims 10 to 12 inserted into a slot of a core.

16. 16. The armature of claim 15, wherein said segment conductors are connected between adjacent ends.

17. 17. The armature of claim 16 which is a stator.

Citation Information

Patent Citations

  • Surface treated aluminum material superior in corrosion resistance, and manufacturing method therefor

    JP2003073853A

  • Insulating material made of aluminum alloy excellent in withstand voltage characteristic and its manufacture

    JP2000349320A

  • Coated alumite having polyimide film and method for producing the same

    JP2004059997A

  • Surface treatment member

    JP2011117042A

  • Anode oxidized aluminum alloy member excellent in voltage resistance

    JP2018044227A